Program evaluation: marriage and family therapy programs' multicultural competency - Culver, Rebecca E. (Kansas State University, 2011)
The purpose of the current study is to examine what factors contribute to how marriage and family therapy (MFT) programs address multicultural competency training and to understand the support mechanisms of the training process. A sequential explanatory mixed-method design was utilized to evaluate MFT training programs. First, a Multicultural Survey, adapted from the Multicultural Competency Checklist (Ponterotto, Alexander, & Griegor, 1995), was used to gain a preliminary understanding of the masters MFT field regarding multitcultural competency training. Out of the 70 MFT program directors contacted, 39 program directors or program representatives responded to the survey (55.71% response). Qualitative interviews from 8 participants (program directors, n = 7; program representative, n = 1) representing each geographical region (Northeast, n = 2; South, n = 2; Midwest, n = 2; West, n = 2) were used to examine programs’ multicultural competency training content, program context and training processes. Five themes emerged from the data: 1) internal program dynamic, 2) external program factors, 3) stakeholders, 4) faculty recruitment, and 5) cross-program collaboration. General systems theory, process theory and the logic model were utilized to conceptualize the results (Kellogg, 2004; Rossi, Lipsey, & Freeman, 2004; White & Klein, 2002).
Keywords: Multicultural competency training; Marriage and family therapy; Multiculturally competent; Program evaluation; Mental Health (0347)